2007
DOI: 10.1152/ajpendo.00617.2005
|View full text |Cite
|
Sign up to set email alerts
|

Muscle glucose transport and phosphorylation in type 2 diabetic, obese nondiabetic, and genetically predisposed individuals

Abstract: Our objectives were to quantitate insulin-stimulated inward glucose transport and glucose phosphorylation in forearm muscle in lean and obese nondiabetic subjects, in lean and obese type 2 diabetic (T2DM) subjects, and in normal glucose-tolerant, insulin-resistant offspring of two T2DM parents. Subjects received a euglycemic insulin (40 mU ⅐ m Ϫ2 ⅐ min Ϫ1 ) clamp with brachial artery/deep forearm vein catheterization. After 120 min of hyperinsulinemia, a bolus of3 H]glucose (tripletracer technique) was given i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 75 publications
0
58
0
1
Order By: Relevance
“…Type 2 diabetes is characterized by insulin resistance and impaired insulin secretion by the pancreas. Insulin resistance causes a reduced insulin-mediated glucose uptake in skeletal muscle, 46 resulting in reduced energy production and weaker contraction of the muscle, especially of type I fibers, 47 which are more common in the muscle of older persons than type II fibers. 48 Furthermore, insulin resistance may lead to muscle protein breakdown.…”
Section: Effect Of Type 2 Diabetes On Body Compositionmentioning
confidence: 99%
“…Type 2 diabetes is characterized by insulin resistance and impaired insulin secretion by the pancreas. Insulin resistance causes a reduced insulin-mediated glucose uptake in skeletal muscle, 46 resulting in reduced energy production and weaker contraction of the muscle, especially of type I fibers, 47 which are more common in the muscle of older persons than type II fibers. 48 Furthermore, insulin resistance may lead to muscle protein breakdown.…”
Section: Effect Of Type 2 Diabetes On Body Compositionmentioning
confidence: 99%
“…The same group studied high fat diet rats showing a defect in skeletal muscle glucose transport under insulin conditions (Halseth et al, 2000), and the influence of muscle www.intechopen.com Nuclear Imaging of Glucose Transport/Metabolism -An Interesting Tool to Screen Insulin Resistance, Refine Diagnosis of Type 2 Diabetes, Understand Disease Mechanisms... 297 fiber types on the rate of insulin-stimulated muscle glucose uptake, with glucose delivery and transport being the primary limiting factors in type II muscle (Halseth et al, 2001;Petersen et al, 2003). Recently, in vivo rates of transmembrane glucose transport and intracellular glucose phosphorylation were determined by analyzing the dilution curves of D-mannitol, [ 14 C]3OMG, and D-[3-3 H]glucose, using a multicompartmental model of glucose kinetics in forearm tissues (Pendergrass et al, 2007). The authors concluded that 1) obese non diabetic, lean type 2 diabetic, and offspring manifest moderate-to severe muscle insulin resistance and decreased insulinstimulated glucose transport and glucose phosphorylation in forearm muscle; these defects in insulin action are not further reduced by the combination of obesity plus diabetes; and 2) the increase in intracelullar glucose concentration under hyperinsulinaemic euglycaemic conditions in obese and type 2 diabetic groups suggests that the defect in glucose phosphorylation exceeds the defect in glucose transport (Pendergrass et al, 2007).…”
Section: -O-methyl-d-glucose (3-omg)mentioning
confidence: 99%
“…Recently, in vivo rates of transmembrane glucose transport and intracellular glucose phosphorylation were determined by analyzing the dilution curves of D-mannitol, [ 14 C]3OMG, and D-[3-3 H]glucose, using a multicompartmental model of glucose kinetics in forearm tissues (Pendergrass et al, 2007). The authors concluded that 1) obese non diabetic, lean type 2 diabetic, and offspring manifest moderate-to severe muscle insulin resistance and decreased insulinstimulated glucose transport and glucose phosphorylation in forearm muscle; these defects in insulin action are not further reduced by the combination of obesity plus diabetes; and 2) the increase in intracelullar glucose concentration under hyperinsulinaemic euglycaemic conditions in obese and type 2 diabetic groups suggests that the defect in glucose phosphorylation exceeds the defect in glucose transport (Pendergrass et al, 2007). Concerning imaging studies, the fact that emission from 18 F can occur at either [ 18 F]FDG or [ 18 F]FDG-6-P, creates implicit uncertainty as to whether compartmental modeling achieves separate estimations of glucose transport and phosphorylation.…”
Section: -O-methyl-d-glucose (3-omg)mentioning
confidence: 99%
“…This state of hyperglycaemia is contributed by three main defects: increased glucose production from the liver, a diminished capacity of the pancreas to secrete insulin and impaired insulin action on muscle and fat , Stumvoll et al 2005. Studies have shown that the primary defect in insulin action in individuals with type 2 diabetes resides predominantly within the skeletal muscle (DeFronzo et al 1981, Utriainen et al 1998, Pendergrass et al 2007. Skeletal muscle insulin resistance is apparent long before the hyperglycaemia becomes evident (Warram et al 1990), as demonstrated in lean, normal glucose-tolerant offspring of parents with type 2 diabetes who have a similar degree of reduced glucose uptake to that of their parents (Gulli et al 1992, Perseghin et al 1997, Ferrannini et al 2003, Tripathy et al 2003.…”
Section: Introductionmentioning
confidence: 99%